2013
DOI: 10.1097/mao.0b013e31827e5fa6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Listening Capabilities and Patient Satisfaction After Stapes Surgery in Otosclerosis

Abstract: Uncomplicated stapes surgery itself is the only predictor of improvement in listening capabilities and patient satisfaction 6 months after stapes surgery in otosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
(20 reference statements)
1
10
0
Order By: Relevance
“…The majority of our study patients (218/239, 91.2 %) reported being right handed, a finding in agreement with the studies on hand preferences in different populations [18][19][20][21]28]. Our findings on female prevalence among the patients with otosclerosis, mean age at presentation for stapes surgery and gender differences in handedness were consistent with those in the literature [2,3,[8][9][10][11][28][29][30][31].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The majority of our study patients (218/239, 91.2 %) reported being right handed, a finding in agreement with the studies on hand preferences in different populations [18][19][20][21]28]. Our findings on female prevalence among the patients with otosclerosis, mean age at presentation for stapes surgery and gender differences in handedness were consistent with those in the literature [2,3,[8][9][10][11][28][29][30][31].…”
Section: Discussionsupporting
confidence: 95%
“…It was found in normal listeners that the right ear (RE) is superior in dichotic listening, monaural speech stimuli, syntax structure, phoneme discrimination, and consonant-vowel recognition [4][5][6][7], whereas,the left ear (LE) is supposed to be superior in nonverbal sound presentation, brief melody listening, and intonation discrimination [4][5][6]. Bilateral otosclerosis (BO) has been reported in 38.9-90 % patients [8][9][10][11][12][13]. The RE advantage in righthanded individuals and the LE advantage in left-handed ones were demonstrated in individuals with a normal hearing and in a population with hearing impairment [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The ABG closure was calculated using the four-tone average for pre- and post-operative air conduction and bone conduction thresholds in 86.3 per cent of the papers; 4 , 6 , 7 , 14 21 , 23 53 , 55 , 59 , 62 however, 3 kHz was only used in 45.1 per cent of these calculations 6 , 7 , 15 , 16 , 20 , 21 , 24 , 28 , 32 34 , 38 , 40 44 , 47 , 51 , 53 , 55 , 57 , 59 . The remaining papers either substituted 3 kHz with 4 kHz (in 79.2 of papers), or averaged 2 kHz and 4 kHz (in 16.7 per cent).…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the use of a self-reported questionnaire was intended to obtain the missing information about the effectiveness of stapes surgery. Looking at research groups in the studies analysed earlier, we note that not all patients gave postoperative observations, in particular long-term ones (1,5,15,18).…”
Section: Limitations Of the Study And Future Directionsmentioning
confidence: 97%
“…Self-reported tools can provide unique insights into the consequences of hearing loss which are unobtainable using conventional objective clinical assessments (14). Although there are a few scientific reports from medical centers around the world which have been published on hearing change after stapes surgery from the patient's point of view, to the best of our knowledge the results of similar prospective studies conducted among Polish patients have not so far been reported (9,10,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%